Educational Java applets get in power electronics labs - Canesin, C. A. [UNESP]; Gonçalves, F. A S [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
This paper presents Java applet programs for a WWW (world wide web)-HTML (hypertext markup language)-based multimedia course in basic power electronics circuits. These tools make use of the benefits of Java language to provide a dynamic and interactive approach to simulate steady-state idealized rectifiers (uncontrolled and controlled; single-phase and three-phase). In addition, this paper discusses the development and the use of the Java applet programs to assist the teaching of basics rectifier power electronics circuits, and to serve as a first design tool for basics power electronics circuits in the experiments of the laboratories. In order to validate the developed simulation applets, the results were confronted with results obtained from a well-know simulator package PSPICE. © 2005 IEEE.
Keywords: Curricula; Engineering education; HTML; Interactive computer systems; Java programming language; Multimedia systems; Java applet; Multimedia courses; Power electronics circuits; Power electronics laboratories; Power electronics